The Effectiveness of Fernald Technique to Improve the Beginning Writing Ability of the Students with Autism in Class V of SLB Luki Padang. Thesis. Special Education Study Program of Faculty of Education of UNP. (SSR di SLB Lubuk Kilangan Padang) - Agusnita Yetni (Universitas Negeri Padang, 2015)
This research was conducted due to a problem found in the filed indicating that a student with autism was not yet able to write well and correctly. She frequently did mistake in writing. This research sought to prove whether the use of Fernald technique could improve the beginning writing ability of the student with autism in class V of SLB Luki Padang. This Single Subject Research applied A-B-A design. The assessment done in this research was consistent on assessing the number of letters written by the student well and correctly. The number of the letters tested in this research was five. The results of the research showed that in the baseline condition, the student’s ability to write was very low in which she was only able to write a letter. After the intervention was given (Fernald technique), the student’s ability to write improved. In the second baseline, her ability also increased. The percentage of her ability in the baseline condition was 20%, in intervention condition was 80% and in the second baseline condition was 80%.The student was able to write four of five letters (a, c, g, i and m) tested and her current ability to write was 80%. Hence, the use of Fernald technique could improve the beginning writing ability of the student with autism at SLB Luki Padang. It was recommended to the teachers to apply Fernald technique in the learning process so that the students could learn more enthusiastically. Keyword: Beginning Writing, Fernald Technique, Students with Autism